+0  
 
0
453
2
avatar

how do i factor out 6x^2-x-1?

Guest Oct 29, 2015

Best Answer 

 #1
avatar+1792 
+10

Since the constant term is -1 you know your factors are going to be

 

\(6x^2 -x -1 = (a x + 1)(b x -1) = (ab)x^2+(b-a)x-1\)

 

\(a b =6, (b-a)=-1 \\ b=a-1 \\ a(a-1) = 6 \\ a=3, b=2\)

 

\(6x^2-x-1 = (3x+1)(2x-1)\)

Rom  Oct 29, 2015
 #1
avatar+1792 
+10
Best Answer

Since the constant term is -1 you know your factors are going to be

 

\(6x^2 -x -1 = (a x + 1)(b x -1) = (ab)x^2+(b-a)x-1\)

 

\(a b =6, (b-a)=-1 \\ b=a-1 \\ a(a-1) = 6 \\ a=3, b=2\)

 

\(6x^2-x-1 = (3x+1)(2x-1)\)

Rom  Oct 29, 2015
 #2
avatar+92919 
0

 

Thansk Rom    smiley

I would not have done it like that but I like that logic.

To use Chris's expression,  "I will put that in my tool belt"

I think that is what chris says anyway LOL

Melody  Oct 29, 2015

8 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.